Upaya Meningkatkan Hasil Belajar Siswa melalui Penggunaan Model Pembelajaran Complete Sentence pada Mata Pelajaran Al-Qur’an Hadits Pokok Bahasan Surat At-Takatsur - Marida, Rida; Tantowie, Tanto Aljauharie (Bestari, 2020)
The objectives of this study were: (1) To improve the ability of teachers in compiling lesson plans on the subject of Al-Qur'an Hadith on the subject of Surat At-Takatsur using the Complete Sentence model in class III MI Cikupa, Werasari Village, Sadananya District, Ciamis Regency; (2) To improve the teacher's ability in the process of implementing learning on the subject of Al-Qur'an Hadith, the subject of the At-Takatsur letter by using the Complete Sentence model in class III MI Cikupa, Werasari Village, Sadananya District, Ciamis Regency; (3) To improve student learning outcomes in the subject of Al-Qur'an Hadith, the subject of the At-Takatsur letter using the Complete Sentence model in class III MI Cikupa, Werasari Village, Sadananya District, Ciamis Regency. The research method used was Classroom Action Research (PTK) using the John Elliot model. This research was conducted in three cycles by carrying out several steps starting from planning, implementing, observing and reflecting. Data collection techniques used were observation, tests, interviews and descriptive analysis. The data collection instrument used was the instrument of observation of the lesson plan, the teacher's research instrument of the learning process and the instrument of student learning outcomes. After analyzing the data, the researchers obtained the following conclusions: (1) The ability of the teacher in compiling lesson plans in the Al-Qur'an Hadith subject using the Complete Sentence model increased, it was proven that in cycle I got an average score of 86.09, including the good category, in cycle II 88.13 is in the good category, and in cycle III 90.02 is in the very good category. (2) The ability of the teacher in the learning process of Al-Qur'an Hadith using the Complete Sentence model increases, it is proven that in the first cycle it gets an average score of 85.32 which is in the good category, in the second cycle 87.54 is in the good category, and in the third cycle 90 is in the good category. (3) The student learning outcomes in the Al-Qur'an Hadith subject using the Complete Sentence model increased, from the first cycle it got an average score of 70.71 including the enough category, in the second cycle 78.33 was in the good category, and in the cycle III 87.14 is in the good category